Critique of Direct Translation Techniques in the African Colonial Novel: A Study of the French Version of “Things Fall Apart”. By (Texas Journal of Multidisciplinary Studies, 2022)
Translating Thing Fall Apart of the Renowned Nigerian writer, Chinua Achebe French is as interesting as it is intriguing. It is very significant today as it promotes a cultural dialogue between the Igbo people of Nigeria and millions of people who speak French and earnestly want to know the different aspects of the Igbo people and their way of life. As they appear in the source text. Pierre Gira, uses different techniques of translation in his efforts to recreate the message and the style of the original work in his version including the direct and indirect techniques. He translates anthroponymes, toponymes, cultural et traditional phenomena among others these techniques are valuable in some respects but many others they are ineffective and fall below expectation. Indeed, a good translation requires a good and informed choice of technique, in order to satisfy the interests of the author and adequately respond to the desires of the readers.